Harmonisasi Budaya dan Agama: komparasi Tradisi Baduy dan Nahdlatul Ulama - Hasani Ahmad Said; Lina Sobariyah; Sahmin Madina (Al-Ulum, 2020)
This study discussed the harmonious life of the Baduy people, a group of indigenous group who still maintain and preserve Pikukuh or traditional taboos that guide activities based on Sundanese Wiwitan teachings. Meanwhile, Nahdhatul Ulama is a religious and cultural identity embraced by most Muslims in the archipelago by preserving traditionalism. Baduy and Nahdlatul Ulama, society and group teachings, uphold the harmonious balance between humans and their gods in the context of life that preserves culture and upholds religion. Baduy preserves local traditions that are not only a reference for the behavior of community groups. However, it is also a source of inspiration for each community to live a compact, albeit different, life. Meanwhile, Nahdhatul Ulama's works are influenced by the social environment in which Islam can be accepted and developed. Finally, culture and religion continue to exist in harmony because they are mutually supportive parts.